circZMYM2 Competed Endogenously with miR-335-5p to Regulate JMJD2C in Pancreatic Cancer - Yong An; Huihua Cai; Yue Zhang; Shengyong Liu; Yunfei Duan; Donglin Sun; Xuemin Chen; Xiaozhou He (Cellular Physiology and Biochemistry, 2018)
Background/Aims: We aimed to study the involvement of circZMYM2 (hsa_circ_0099999) in pancreatic cancer (PC) cell proliferation, apoptosis and invasion and to figured out the underlying mechanism of circZMYM2 regulating miR-335-5p and JMJD2C. Methods: CircRNA differential expressions in twenty PC samples and paired normal tissue samples were analyzed using Arraystar Human CircRNA microarray V1. CircZMYM2 expression level was determined via qRT-PCR. The effects of circZMYM2 inhibition and overexpression on cell proliferation, cell apoptosis and cell invasion were investigated by CCK-8 assays, Flow cytometry assays and Transwell assays. An animal experiment on nude mice was put forward to test the influence of circZMYM2 knockdown on tumor growth. The relationship between circZMYM2, miR-335 and JMJD2C was verified by RNA pull down, dual-luciferase reporter assays and rescue experiment. The effect of circZMYM2 and miR-335-5p on the expression of JMJD2C protein was detected by western blot. Results: CircZMYM2 overexpression was observed in both PC tissues and cells. Knockdown of circZMYM2 inhibited proliferation, induced apoptosis, and weakened invasion ability of cancer cells. Tumor growth was restrained in vivo. CircZMYM2 repressed the expression of its target miR-335-5p. MiR-335-5p attenuated pancreatic cancer development via inhibition of JMJD2C. Conclusion: Our study demonstrated that circZMYM2 promoted PC progression. CircZMYM2 had a sponge effect on miR-335-5p and modulated the downstream oncogene JMJD2C.